2011
DOI: 10.5005/jp-journals-10071-23376
|View full text |Cite
|
Sign up to set email alerts
|

Extended Continuous Infusion of Methylene Blue for Refractory Septic Shock

Abstract: Objective: Highlight the utility of methylene blue (MTB) infusion for extended period for refractory vasoplegia. Introduction: Hypotension refractory to vasopressor therapy in sepsis is associated with high mortality and limited therapeutic options. Dysregulated nitric oxide (NO) pathway seems to be a major driver, and, therefore, MTB, which inhibits inducible NO synthase activity and decreases cyclic guanosine monophosphate (GMP) accumulation by directly competing with NO by binding to soluble guanylyl cyclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…If the cases are treated with ECMO, the mortality rate will be up to 80% [11]. In accordance with some case reports [44], the clinically highest dosages of various vasopressor drugs and the prolonged MB infusion during the VV-ECMO treatment may reverse RSS.…”
Section: Application Of Ecmo In Combination With Methylene Blue (Mb) ...supporting
confidence: 64%
“…If the cases are treated with ECMO, the mortality rate will be up to 80% [11]. In accordance with some case reports [44], the clinically highest dosages of various vasopressor drugs and the prolonged MB infusion during the VV-ECMO treatment may reverse RSS.…”
Section: Application Of Ecmo In Combination With Methylene Blue (Mb) ...supporting
confidence: 64%
“…Although a multitude of experimental studies have documented favorable hemodynamic effects, the clinical evidence supporting the use of MB is predominantly derived from case reports, small observational studies, and a limited number of controlled trials. 12 , 13 Despite the observed improvements in MAP and systemic vascular resistance (SVR) following the administration of MB, the evidence supporting a statistically significant improvement in survival outcomes remains inconclusive. 10 , 14 16 …”
Section: Discussionmentioning
confidence: 99%
“…Patients are always closely monitored for any potential adverse effects in RCTs, and although our results could be considered as reassuring, we recognize the importance of post-marketing drug safety surveillance in real-world settings, and urge clinicians to strictly adhere to specifications of manufacturers along with local pharmacy department policies. Notwithstanding, we would like to pinpoint other pharmacokinetic/pharmacodynamic factors that could have improved the efficacy of MB in our trial even more than the use of NS; namely, an initial 1 mg/kg bolus [ 10 ], doses of 2–3 mg/kg instead of fixed 100 mg [ 11 13 ], continuous infusion [ 4 , 14 ], repeated doses until shock resolution instead of a fixed 3-doses scheme, and especially, aiming for an earlier administration after septic shock diagnosis, as it has been suggested that efficacy could be enhanced if MB is used within the first 8 h [ 15 ].…”
mentioning
confidence: 99%